Ketidaksetaraan KETIDAKSETARAAN DALAM HAK WARIS ADAT BATAK : TINJAUAN TERHADAP PRAKTIK DAN IMPLEMENTASI - Simorangkir, El Given; Puspita Sari, Sartika; Arbina Mutiara Idris, Kesha (Paradigma POLISTAAT: Jurnal Ilmu Sosial dan Ilmu Politik, 2023)
Highly motivated fresh graduate with experience in customer service and business coordination, seeking the position of Gas Coordinator. The rise of equality issues has led to demands to remove inequalities between women and men, especially regarding inheritance. The upheaval of women against inequality in the patrilineal system can result in internal conflicts, even reaching lawsuits in the family concerned. The purpose of this research is to find out how the distribution of inheritance rights in Batak customs, and data collection techniques through interviews. In this study, the authors used analytical descriptive qualitative methods. The author uses the descriptive analytical method because this method can answer research problems coherently and in detail. Researchers collect data used in research through literature study. The results of this study indicate that Batak customary law does have a striking difference in the distribution of inheritance rights, because men as the successor of descent are patrilineal while women only continue the lineage of other men (husbands), so with property inheritance, the most important thing is that the new man is given a share by the man (husband) and the witness of the family guardian, namely his mother's brother. However, if there are only daughters in the family, adat will determine and award it to the closest lineage to the main clan family and can be according to the will of the nuclear family.